(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Promotion includes all marketingactivities aimed at stimulating demand and demand can be stimulated bycommunicating with market. Thus the genesis of promotion or promotional effortslies in effectively communicating with the market. The word communication isderived from a Latin word which means ’to share’ and more fundamentally fromthe rootword ’communize’, which means common communication involving sharingspecific message with a target audience